Healthy food intake advisor using decision support system - Lee, Jia Hwee; Witarsyah, Deden; Kasim, Shahreen; Md Fudzee, Mohd Farhan (IJSTR, 2020)
: The difficulties to decide the food to eat and do not have enough knowledge that what foods should be avoided when pregnant or when facing some health problem. Healthy Food Advisor is an Android based application which acts as a healthy controller to all of the users. The purpose of developing this application is to suggest healthy food to users based on their personal condition in order to make them have a healthy lifestyle. Users are required to record all of the details such as age, height and weight, so the application and calculate the Body Mass Index (BMI) value and ca loric needs to user. Application will recommended the most suitable food lists to users according to their personal condition. Through this application, users no longer need to spend more time to think on a meal and busy to search from online that the nutrition information of food. The methodology used to develop this Android based application is Object-oriented Software Development (OOSD) model. Software technology used to develop this application is Ionic Framework where this technology uses web technology language to develop mobile hybrid application. Database used for this system is Firebase while programming language used to develop this application is AngularJS, HTML, TypeScript and SCSS. Hereby, this application is able to provide a simple and portable solution to help people decide the food and increase the knowledge of the public.